2022
DOI: 10.1038/s41467-022-32544-1
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for shape-selective recognition and aminoacylation of a D-armless human mitochondrial tRNA

Abstract: Human mitochondrial gene expression relies on the specific recognition and aminoacylation of mitochondrial tRNAs (mtRNAs) by nuclear-encoded mitochondrial aminoacyl-tRNA synthetases (mt-aaRSs). Despite their essential role in cellular energy homeostasis, strong mutation pressure and genetic drift have led to an unparalleled sequence erosion of animal mtRNAs. The structural and functional consequences of this erosion are not understood. Here, we present cryo-EM structures of the human mitochondrial seryl-tRNA s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 74 publications
2
28
0
Order By: Relevance
“…Most tRNAs encoded in human mitochondria are highly degenerate, and differ significantly in sequence, structure, and stability from canonical tRNAs encoded in the nucleus 28,63 . Most notably, mt-tRNAs often lack universally conserved tRNA structural features that are used by many tRNA-processing factors to recognize nu-tRNAs 23,28,35,40 . ELAC2 catalyzes tRNA 3'-processing both in the nucleus and mitochondria 31,42,49 , and thus must recognize pre-tRNAs from both compartments.…”
Section: Discussionmentioning
confidence: 99%
“…Most tRNAs encoded in human mitochondria are highly degenerate, and differ significantly in sequence, structure, and stability from canonical tRNAs encoded in the nucleus 28,63 . Most notably, mt-tRNAs often lack universally conserved tRNA structural features that are used by many tRNA-processing factors to recognize nu-tRNAs 23,28,35,40 . ELAC2 catalyzes tRNA 3'-processing both in the nucleus and mitochondria 31,42,49 , and thus must recognize pre-tRNAs from both compartments.…”
Section: Discussionmentioning
confidence: 99%
“…When preorphan GlyRS evolved to more accurately and effectively capture tRNA Gly by integrating an ABD, the ABD was not obtained from other class IIa aaRSs but from ArgRS, because the ABD of ArgRS has multiple specific interactions with C35 of tRNA Arg . For other tRNAs with C at position 35, their corresponding aaRSs recognize tRNA either through the shape of the cognate tRNA [e.g., seryl-tRNA synthetase (SerRS) and cysteinyl-tRNA synthetase (CysRS)] or by forming more interactions with another nucleotide in the anticodon loop [e.g., trytophanyl-tRNA synthetase (TrpRS)] ( 29 , 54 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest a more critical role of the C-terminal tail for binding hmtRNA Ser (AGY) in catalysis, in accordance with the previously reported results ( 19 ). Indeed, a very recent study has reported the cyro-EM structure of SARS2-tRNA Ser (AGY), which clearly shows that the very C-terminus provides an important interaction site for binding the T-stem sugar-phosphate backbone of tRNA Ser (AGY) ( 54 ).…”
Section: Discussionmentioning
confidence: 99%